Cascade decode-and-forward: spatial diversity reuse in sensor networks. (2016) - Wang, Siyi; Guo, Weisi; Jafari, Amir
In this paper, we consider a wireless sensor network that involves data transmitted through multiple relays to reach a destination. In particular we improve the decode-and-forward cooperative relaying scheme, by proposing the Cascade-Decode-and-Forward scheme, where the number of successful relays increases with each additional cooperation stage. The achieved effect is a cascade of relays that contribute towards achieving full spatial diversity at the destination. A relationship between the achievable bit error rate and delay is derived for the proposed scheme. The results show that for a small delay constraint, the scheme can achieve full diversity. As the delay constraint increases, the protocol can achieve full diversity at signals levels 10-100 orders magnitude lower than the decode-and-forward protocol. The proposed protocol can dynamically trade-off transmission reliability with delay and a certain node connectivity density is required to achieve a cascading cooperation chain with an arbitrary low data extinction probability.